Investigating the Collaborative Process of Subtitles Creation and Sharing for Videos on the Web - Brito, Jessica Oliveira; Guimaraes, Rodrigo Laiola; Santos, Celso A. S. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
In this paper we concentrate on the study of the collaborative practices of enthusiasts that create and share subtitles for thirdparty videos. Based on preliminary results from interviews with some volunteers, we formalize the subtitles creation and sharing process using a business process management model and compare it with other collaborative and crowdsourcing models. We expect that our initial observations can bring a new understanding of the process and, thus, help in the design of next generation video enriching tools.